PROFILE OF STUDENT’S AND TEACHER’S ABILITY TO UTILIZE DIGITAL DEVICE IN THE LEARNING OF IPAS AT SDN BUNULREJO 1 MALANG - Rahmawati, Iin Nur Indah; Febrianti, Aristhalia Hevi; Wibowo, Agus Mukti; Sugiri, Wiku Aji; Kurniawan, Prayoga Tri (Proceeding of International Conference on Islamic Education (ICIED), 2023)
Recent developments in digital technology have occurred massively. This research aims to describe the ability of teachers and students to utilize technological devices for learning. This research uses a qualitative method with a descriptive approach. The tool used in the research was a closed questionnaire complemented by structured interviews. The research subjects were teachers and students of class IV-C, SDN Bunulrejo 1 Malang. To check the validity of the data, triangulation was carried out on the information that had been obtained. The research results show that teachers and students have a good ability to use technology. Teachers are accustomed to learning models that utilize digital technology. Some applications that teachers often access are Canva, Quizzizz, Zoom Meeting, Google Meet, Edmodo, and Google Classroom. Meanwhile, students are used to using technology such as smartphones and tablets. They have these facilities in their respective homes. They are familiar with digital devices from an early age. Students are used to playing games and watching videos via their gadgets. These findings provide opportunities for the development of science and technology learning that is integrated with technology. This research has become the initial part of the intended learning development.